LINGUISTIC AND STYLISTIC REPRESENTATION OF EMOTIONS IN LITERARY TEXTS AND ITS IMPACT ON READERS - Kalmuratova, Juldız Rustemovna (SCIENCE and SOCIETY, 2026)
Reading literary works is viewed not only as a leisure activity but as a process of deep emotional empathy. The article analyzes the linguistic and narrative strategies employed by authors to depict the internal world of characters and establish a connection with the reader. Through empathizing with the characters during moments of conflict and transformation, the reader interprets complex human experiences. The study focuses on how linguistic tools ensure emotional engagement and allow the reader to achieve a resonance with the characters’ feelings.